Work-based learning : towards embedded processes and inclusive approach - Kersh, Natasha [Verfasser]; Laczik, Andrea [Verfasser]; Evans, Karen [Verfasser]; Emms, Katharine [Verfasser]; Maslo, Irina [Verfasser]; Ertl, Hubert [Verfasser] (My University, 2021)
"The context for this paper is strongly underpinned by the significance of the integration of education and the world of work, which has been recognised as a key issue for policy, practice and research across Europe and beyond. The four interrelated symposium papers focus on the complexities of work-based learning and explore its different configurations. The potential of a social ecological approach for exploring the relationships between work and learning will be considered. The papers will further draw on perspectives from three European countries: Germany, Latvia and the UK. Through these three cross-national case studies, the context of the workplace has been considered as a crucial indicator of different dimensions of work-related learning. The papers identify some influential interdependent and embedded processes involved, such as the consolidation of theory and practice, digitalisation, personalised workplace learning patterns and crossing boundaries between different sectors, approaches and learning routes such as work-based and Higher Education. In these processes, the central place of agency of the learning individual, needs to be taken into account, and the social ecological approach provides a useful framework to capture the interdependent, relational and contextually embedded developments involved. Through these three case studies, this paper aims to facilitate cross-national discussion of the complex nature and changing demands of contemporary work-based learning, particularly highlighting the significance of its inclusive perspective and embedded approaches." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; T 4.5 Soziologie; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; 370; Beziehung Bildungssystem Beschäftigungssystem; Berufsbildung; Hochschulbildung; Lernen am Arbeitsplatz; Digitalisierung; soziale Umwelt; Sozialisationsforschung; Internationaler Vergleich; Fallstudie; Bundesrepublik Deutschland; Vereinigtes Königreich; Lettland; Learning Analytics; VUKA-Welt